Mongolian distinction on horse coloration - Y. Konagaya (Nomadic Civilization: Historical Research, 2023)
This report is an extension of the author’s presentation at the Tenth Forum on Northeast Asian Ethnic Cultures held on November 15, 2019, at the Central University for Nationalities under the auspices of the Society for the Study of Northeast Asian Ethnic Cultures of the Chinese Ethnological Society. The presentation was given in Mongolian and interpreted into Chinese. Although this international symposium could have been held to celebrate the development of One Belt, One Road, no collection of papers is expected to be published until 2022. This article is the English translation of Japanese original text “Mongol ni okeru Uma no Keiro ni kansuru Bunruimeisho no Meineigenri” written by Yuki Konagaya and published in 2022 in “Biostory” (2022, 38: 85-94). According to the wide variety of horse coat colors, there are many Mongolian words. In this article several main folk terms of horse coat color are clearly classified and you can grasp how people categorize the terms according to the key criteria of their taxonomy. These folk terms are very useful for nomads specially when they should find the missing horses that usually graze autonomously far away from the campsite.